Evaluation of the performance and gas emissions of a tractor diesel engine using blended fuel diesel and biodiesel to determine the best loading stages - Haitham Emaish (Nature Portfolio, 2021)
Abstract Fossil fuels are the main energy sources responsible for harmful emissions and global warming. Using biodiesel made from waste deep-frying oil as an alternative fuel source in diesel engines has drawn great attention. This biodiesel is produced using the transesterification process and blends with mineral diesel at Faculty of Agriculture Saba Basha, Alexandria University, Egypt. The turbocharged diesel engine of a Kubota M-90 tractor was tested. The objectives of this work are to test tractor as a source of power in the farm using waste deep-frying oil biodiesel to utilize waste frying oils (WFO) in clean energy production on the farm and determine the best engine loading stages to maximize engine efficiencies for different fuel blends and reduce the environmental impact of gas emissions from tractor diesel engines in the farms. The experiment design was factorial, with two factors, where the first was the engine load (0%, 25%, 50%, 75%, and 100%) and the second was fuel blend (0%, 5%, 20%, and 100% biodiesel), and the effects of loading stages and biodiesel percentage on engine performance indicators of engine speed, power take off torque, power take off power, brake power, brake mean effective pressure, brake thermal efficiency, brake specific fuel consumption, and gas emissions were studied. The experimental results indicated that engine load percentage and fuel blend percentage significantly affected all studied characters, and the best engine loading stages were between 25 and 75% to maximize engine efficiency and minimize the specific fuel consumption and gas emissions. Increasing the biodiesel percentage at all loading stages resulted decreasing in Engine brake power (BP), brake thermal efficiency, Power take-off (PTO) torque, and brake mean effective pressure and increases in brake specific fuel consumption. Increasing the engine load resulted in decreases in O2 emissions and increases in CO2, CO, NO, and SO2 emissions. Increasing the biodiesel percentage in the blended fuel samples resulted in increases in O2 and NO emissions and decreases in CO2, CO, and SO2 emissions. The use of biodiesel with diesel fuel reduces the environmental impact of gas emissions and decreases engine efficiency.